The relationship between the timing of take-off action and flight length by using the doll-model - Sasaki, T.; Tsunoda, K.; Hoshino, H.; Miyake, S.; Ono, M. (Science and Skiing IV, 2008)
Introduction: In ski jumping, take off ground is a only place at which the jumper can change their moving direction. Therefore, it is important to know how the take off motion affects the jump length, If jumpers have same power, the timing of power production could mostly affect the flight length. But, it is impossible to make same power production come true in human performance. If the jumping hill could be reduced to one hundred, take-off speed is approximately 1 or 2 m/s. Then the aerodynamic force can be ignored. The flight length depends on the take off velocity, which changes both the speed and moving direction with jump action. It is important to know the behavior of jumping performance. Especially, it is important to know when the jump action Starts. Taking this into serious consideration, we tried to clarify the Optimum timing of the jump action by using a compact jumping doll which four springs is incorporated.